.LINGUO-CULTURAL CHARACTERISTICS OF EDUCATIONAL AND NEWLY EMERGING WORDS IN THE WORKS OF ABDULLA QODIRIY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
this article presents considerations on the educational terms used in the works of Abdulla Qodiriy, their internal classification, their meanings, reasons for use, the emergence of neologisms, their use in oral speech in a changed form, and their linguo-cultural characteristics.